Projeto winnicottiano: as transformações do setting na psicanálise modificada com pacientes borderline - Manzano, Valquiria Cruz (2020)
Throughout the history of psychoanalysis, as the knowledge of clinical conditions has expanded, the setting and technique have also been modified. The objective of this study, which is basically located in the field of the winnicottian project: it consists of knowing more about some resources that make up the modifications of the setting proposed by Winnicott, those that are distinguished at the limit of the standard analysis that, throughout the analysis of the Margaret case Little, came to prove to be of value in the scope of treatment and expanding the psychoanalytic resources by territories until then little explored. In order to carry out this study, the Margaret Little case was used and her analysis with Donald Winnicott, as she described it, as well as a summary of her two previous analyzes both unsuccessful. In certain patients with certain clinical conditions, such as, for example, borderline type, such as Margaret Little, these had their emotional maturation interrupted, due to traumatic environmental failures, presenting with fragile egos, the classic setting was not usable. So, the winnicottian project proposes a setting that provides the analytical holding and in this environment support is provided for the analytical situation, and the patient can regress within the process of regression to the phases of absolute dependence, that is, at the moment when maturation was interrupted. Due to environmental failure and, thus, it is possible to thaw traumatic situations and offer the patient the possibility to allow his emotional maturation. Thus, offering our patients a setting as a facilitator of emotional maturity, the analyst being able to have more resources to face the multiple faces of contemporary man's suffering